Gene expression profiles in peripheral blood mononuclear cells correlate with salience network activity in chronic visceral pain: A pilot study. Issue 6 (12th February 2017) - Gupta, A.; Cole, S.; Labus, J. S.; Joshi, S.; Nguyen, T. J.; Kilpatrick, L. A.; Tillisch, K.; Naliboff, B. D.; Chang, L.; Mayer, E. A.
Abstract: Background: Distinct gene expression profiles in peripheral blood mononuclear cells (PBMCs) consistent with increased sympathetic nervous system activity have been described in different populations under chronic stress. Neuroinflammatory brain changes, possibly related to the migration of primed monocytes to the brain, have been implicated in the pathophysiology of chronic pain. Irritable bowel syndrome (IBS) is a stress‐sensitive gastrointestinal disorder associated with altered brain‐gut interactions and increased sympathetic/vagal tone and anxiety. Reports about immune alterations in IBS are conflicting. This pilot study aimed to test how PBMC gene expression inflammatory profiles are correlated with altered brain signatures in the salience system. Methods: Sixteen IBS and 16 healthy controls (HCs) completed resting state MRI scans. Gene expression profiles in PBMCs were assessed using human transcriptome array‐2. Bioinformatic analyses determined differential expression of PBMCs between IBS and HCs. Partial least squares, a multivariate analysis technique, was used to identify disease correlations between PBMC gene expression profiles and functional activity in the brain's salience network. Key Results: Regions of the salience network, including the mid cingulate cortex, and mid and superior temporal gyrus were positively correlated with several pro‐inflammatory genes (interleukin 6, APOL2) in IBS, but negatively correlated with several anti‐inflammatory genes (KRT8, APOA4) in HCs. Conclusions & Inferences: Based on rodent studies, one may speculate that chronically activated stress signaling pathways in IBS maintain a pro‐inflammatory state in the periphery. Alternatively, primed monocytes may migrate to the brain during stress, inducing regional neuroinflammatory changes in salience regions involved in the modulation of visceral sensitivity. Abstract : Results show a difference in correlation between PBMC gene expression levels and salience network connectivity in patients with IBS vs. HCs. Inflammatory genes (IL6 and APOL2) are positively correlated with connectivity within salience network in IBS patients (strengthened connectivity). Genes with anti‐inflammatory properties (KRT8, APOA4, KRT8A) and 1 inflammatory gene (APOL2) are negatively correlated with connectivity within salience network in HCs (weakened connectivity.